Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor Roda Dua Di Kota Bekasi - Samela, Novi; Siringoringo, Whereson; Hotang, Keri Boru (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2024)
Purpose – This study aims to determine taxpayer awareness, tax rates and tax sanctions, taxpayer compliance in paying motor vehicle tax. Design/methodology/approach – This research was conducted at the SAMSAT Bekasi City office, using accidental sampling method with data collection carried out using questionnaires as many as 104 respondents, data analysis using percentage descriptive analysis, multiple regression analysis and hypothesis testing through partial testing. Findings – The results showed that tax awareness and tax rates did not have a significant effect on motor vehicle taxpayer compliance. Meanwhile, tax sanctions have a significant effect on taxpayer compliance. Research limitations/implications – An increase in the number of motor vehicles can provide an increase in government revenue, the importance of increasing revenue for the government, so the author re-examines the factors that affect motor vehicle taxpayer compliance because there are still inconsistent positive results from several previous studies.